ANALISIS KESEHATAN FISKAL DAERAH: STUDI PADA APBD KABUPATEN MOJOKERTO 2018 - Vidya Imanuari Pertiwi; Oktarizka Reviandani (Journal Publicuho, 2022)
Fiscal health is an abstract fiscal condition which cannot be directly observed and measured accurately. Local governments in Indonesia have the authority as a result of regional autonomy to regulate and manage budgets. However, not all regions are able to utilize this authority properly. The purpose of this article is to see how healthy budgeting practices are in one of the regions in Indonesia, in this case, Mojokerto Regency. The method used is qualitative with content analysis in the 2018 Mojokero Regency Revenue and Expenditure Budget. The results of this study are that the Mojokerto Regency government faces problems related to budget deficit estimation. Other problems also include regional dependence on the central government. The limitation of this research is that the analysis is carried out with the 2018 budget documents, so further analysis is needed with the latest documents.